2011
DOI: 10.1007/s16024-011-0239-9
|View full text |Cite
|
Sign up to set email alerts
|

Ernährungsgewohnheiten, BMI und Diätversuche von Auszubildenden in Gesundheitsfachberufen

Abstract: ZusammenfassungEinleitung und Zielstellung: Ungesunde Ernährung, Übergewicht und Diäten stellen selbst bei Auszubildenden in Gesundheitsfachberufen ein Problem dar. Da bislang nur wenige entsprechende Studien vorliegen, sollten das Ernäh-rungsverhalten, das selbst berichtete Gewicht und die Zahl der Diätversuche bei Auszubildenden der Gesundheitsfachberufe untersucht werden. Methodik: An einer Medizinischen Berufsfachschule wurden bei einer Vollerhebung 433 standardisierte anonyme Fragebögen an Auszubildende i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Overweight is an indicator for health behaviour and a factor influencing the health status. A mean prevalence of 30 % of overweight was assumed among apprentices [12, 13]. For a 95 % chance of our sample estimate being within five percentage points of this assumed prevalence (30 ± 5 %), a sample size of n  = 322 was needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight is an indicator for health behaviour and a factor influencing the health status. A mean prevalence of 30 % of overweight was assumed among apprentices [12, 13]. For a 95 % chance of our sample estimate being within five percentage points of this assumed prevalence (30 ± 5 %), a sample size of n  = 322 was needed.…”
Section: Methodsmentioning
confidence: 99%
“…The highest proportion (45 %) of overweight and obesity among nursing students was found in the US [17]. Rates reported by German studies of apprentices in the nursing field ranged from 20 to 32 % [12, 13]. A German survey reported that 58 % of apprentices at nursing schools consumed fast food at least once a week [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on outpatient caregivers and trainees in nursing professions in Germany have indicated that the eating behaviour needs to be improved [8,36,39]. While the literature on fruit and vegetable consumption among nursing and residential care trainees is inconsistent [39][40][41], increased consumption of sweets [39,42] and convenient foods [39] has been reported.…”
Section: Eating and Drinking Behaviourmentioning
confidence: 99%
“…Various studies on outpatient caregivers and trainees in nursing professions in Germany have indicated that the eating behaviour needs to be improved [8,36,39]. While the literature on fruit and vegetable consumption among nursing and residential care trainees is inconsistent [39][40][41], increased consumption of sweets [39,42] and convenient foods [39] has been reported. In addition, a high caffeine consumption as well as obesity have been described as being a consequence of the working conditions and work-related stress perception in the inpatient care [36,43].…”
Section: Eating and Drinking Behaviourmentioning
confidence: 99%
“…A survey at a regional college for health care professions in 2008 showed that overweight, physical inactivity and smoking and alcohol consumption were quite common. Approximately 40% of the surveyed nursing students were smokers, 40% alcohol consumers and 20% were overweight or obese [13,14]. …”
Section: Introductionmentioning
confidence: 99%